CONTRIBUTION OF HUMAN RESOURCES COMPETENCE AND SUPERVISION TO THE PERFORMANCE OF EMPLOYEES IN THE BAGIAN PERSIDANGAN DAN PROTOKOL SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN TULANG BAWANG - Rafian Joni; Junaidi .; Refi Arieon; Sugeng Priyono (University of Sang Bumi Ruwa Jurai, 2021)
The purpose of this study was to determine the influence of competence and supervision on employee performance. The hypothesis in this study is that there is an influence of competence and supervision either partially or simultaneously on employee performance. The sample used in this study amounted to 36 employees. Data collection techniques include observation, documentation and questionnaires. The data analysis method used a quantitative approach with the help of SPSS version 21.0 statistical tools including the calculation of the validity test, reliability test, linear regression test, t test, F test and coefficient of determination test. The results of testing the hypothesis of the influence of competence on performance partially show that competence has a positive influence on performance with a contribution of 50.6%. Supervision has a positive influence on performance with a contribution of 41.3%. Simultaneous hypothesis testing shows that competence and supervision together have a positive influence on performance